Bidimensional extensions of cobalancing and Lucas-cobalancing numbers - Chimpanzo, J.; Otero-Espinar, M. V.; Borges, A.; Vasco, P.; Catarino, P. (Annales Mathematicae Silesianae, 2023)
A new bidimensional version of cobalancing numbers and Lucasbalancing numbers are introduced. Some properties and identities satisfied by these new bidimensional sequences are studied.